PERANCANGAN MESIN PENGERING RIMPANG UNTUK RUMAH PRODUKSI JAMU CELUP TRADISIONAL - Meditama, Ratna Fajarwati; Purwady, Ary Kusuma (Steam Engineering, 2024)
Rhizomes are one of the main ingredients in the production of traditional herbal medicine, which plays an important role in the food, beverage and medicine industries. The process of drying rhizomes greatly affects the quality and shelf life of the product, so an efficient drying device is needed to ensure optimal quality. This research aims to design a rhizome drying tool for traditional dipping herbal medicine production houses, which can speed up the drying process and maintain the quality of the rhizomes produced. This type of research is development research with the research object being rhizomes used in herbal medicine production. Data was collected through testing the designed tool, using temperature and drying time testing methods. Data analysis was carried out by measuring the quality of the rhizomes post-drying, including moisture and color. The research results showed that the designed dryer was capable of drying rhizomes at a temperature of 40°C within 1 hour, while maintaining the quality of the rhizomes and meeting the standards for herbal medicine production. In conclusion, this tool has the potential to be a practical solution for traditional herbal medicine production houses, speeding up the production process and increasing efficiency.